Impact of radiative forcing of spatially varying CO2 concentrations on net primary production - Peng, Jing; Dan, Li; Tang, Xiba; Yang, Fuqiang (Frontiers in Earth Science, 2022)
Radiative forcing of carbon dioxide (CO2) concentration drives variations in the spatial pattern of the global carbon cycle. However, due to anthropogenic emissions, spatial differences in CO2 have increased. The relationship between climatic variables and net primary production (NPP) can be adjusted through the radiative forcing of this amplified spatial non-uniformity. Results show that, owing to radiative forcing of heterogeneous CO2 concentrations, NPP has reduced globally by −0.6 Pg C yr-1. Region 2 with increased CO2 and decreased NPP shows the greatest reductions by −0.7 Pg C yr-1. Variations of both NPP and CO2 concentrations are distributed asymmetrically. As human activities are mainly located in the Northern Hemisphere, increased CO2 has mainly manifested in these regions. Especially in region 2 with increased CO2 and decreased NPP Increasing downward longwave radiation has heated the ground surface by 2.2 W m-2 and raised surface temperatures by 0.23 ℃. At the same time, due to radiative forcing of spatial variations CO2 concentrations, local dependence of NPP on soil moisture has increased due to enhanced temperature and ET coupling, which may improve negative NPP anomalies locally, especially in region 2.